EASTERN LATVIA IN THE GEOSPATIAL POETICS OF NATIONAL ROMATICISTS - Lāms, Ojārs (Via Latgalica, 2017)
The collected efforts of the national romanticists mark a longing for one’s own path within the Latvian cultural landscape, and emphasise the use and understanding of geography and space. The goal of this study is to ascertain – whether and how the created geo-spatiality of the national romanticists stands within the context of Eastern Latvia, which was administratively separated from the rest of the ethnographically collective territories, being a constitutive part of the Vitebsk Governorate. The organic tethering of separated regions was already torn in the 17th century, when Eastern Latvia remained under the control of Poland after the conquering of the collapsed remains of Livonia. Catholicism, idiosyncratic agricultural traditions, unprecedented development of language and writing – the peculiarities discerning Eastern Latvia from the coastal territories are justifiably multifarious. However, one must as well keep in mind the underlying similarities of east and west with the forming of the Latvian nation in the 19th century. The main topic of this paper is the geospatial poetics of the national romanticism, though for the sake of a broader historical context and understanding, it is prefaced by a chapter of “An Account of Associative Preconceptions and Histories of Eastern Latvia in Context of Baltic Provinces”, paying attention to the specific vernacular with which the Latvian landscape is described during the 19th century and closer inspection still to the administrative border between the Baltic provinces and the Governorate of Vitebsk, which holds the Eastern Latvian territories. In the second chapter – “Vitebsk-Latvian Identity from the Viewpoint of Latvian Nationalist Ideological Leaders” – reviews the pre-existing notions which are found in the writings of Krišjānis Valdemārs and Atis Kronvalds and reveals on the one hand a deep vocation of the destiny of the Vitebsk Latvians, though on the other – a somewhat simplified overview. The third chapter directly examines how these preconceived and associative ideas were produced in the many periodicals and publications by the various Latvian communities of the Baltic provinces. The most significant textual sources are travel notes, in which the spatial differences and also visually distinctive features in agricultural tradition are emphasized. The fourth chapter looks at the collectively written works of the national romanticists within the aspects of geospatial imagery, bringing out three levels – the motifs of rivers and lakes, motifs of mountains, alleys and fields, as well as the motif of ancient historical locations, which all together make the illusory mythos of Latvia, within which Eastern Latvia resides. Nevertheless, the geospatial contours of Latvia are only complete with the addition of Eastern Latvia’s local identity – Latgale – which colours the collective Latvian borders with unique geospatial impressions (imagery).